Pengaruh Permainan Tradisional terhadap Perkembangan Motorik Pada Siswa - Dwi Wulan Joy Lumbantobing; Nabila Syahara; Nursari Wahyuni Sigalingging; Rani Natalia Purba; Fajar Sidik Siregar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Children have a strong affinity for games. In daily life, they frequently engage in both traditional and modern forms of play. These games are often viewed as essential tools for promoting children's physical and motor development, which is a critical aspect of early childhood growth. Developing motor skills is a fundamental requirement for young children, and one effective approach to fostering this development is through traditional games. This study examines the role of traditional games in enhancing children's motor skills. By engaging in these activities, it is anticipated that children will not only improve their motor abilities in a more effective and enjoyable manner but also benefit in other areas. Traditional games contribute to a child's development by: 1) promoting physical fitness, resilience, competitiveness, and overall well-being; 2) fostering mental attributes such as sportsmanship, tolerance, discipline, and a sense of democracy; 3) nurturing moral qualities including responsiveness, sensitivity, honesty, and sincerity; and 4) enhancing social skills, enabling children to compete, collaborate, practice discipline, exhibit friendliness, and develop a sense of national identity.